Stereoselective Synthesis of β-Thiolated Aryl Amino Acids - Zheng, Mengjie; Yin, Hongli; Wang, Siyao; Wang, Ping (Synthesis, 2022)
A variety of β-thiolated aryl amino acids were readily synthesized in moderate to excellent yields via 1,4-addition from a readily-accessible thiazoline precursor, which can be prepared from cysteine methyl ester hydrochloride in just three steps. The thiolated products can be subsequently deprotected within one single step in high yields and used directly for subsequent solid-phase peptide synthesis.
Keywords: β-thiolated amino acids; Giese reaction; Michael reaction; cysteine surrogates; native chemical ligation